Education based on theory of planned behavior over sexual function of menopausal women in Iran - Zeinab Jalambadani; Gholamreza Garmaroodi; Mehdi Yaseri; Mahmood Tavousi; Koroush Jafarian (Wolters Kluwer Medknow Publications, 2017)
Background: More than half of the sexual problems in menopausal women are due to insufficient knowledge or false beliefs about sexual function. Theory of planned behavior (TPB) is one of the important theories that explain the main process of adopting healthy behaviors. This study investigates the effect of education based on TPB over sexual function of menopausal women in Sabzevar, Iran. Materials and Methods: In this quasi-experimental study, the data were collected through a survey. This study included 180 Iranian menopausal women from five health center of Sabzevar city in Iran from 2016 to 2017. Using a questionnaire, demographic, anthropometric, and TPB by SPSS version 22 software were measured and analyzed. Results: After educational intervention, the average rates of knowledge, attitude, perceived behavioral control, and intention to sexual function in education group were increased meaningfully (sig <0.05); these changes were not meaningful in control group. Furthermore, there was no statistically meaningful difference in subjective norms between two groups after intervention. Conclusion: According to the findings, it is proposed that TPB be used to improve sexual function in Iranian menopausal women.